Methodological foundations of the comparative-historical studies of Ukrainian linguists of the 70’s of the ХІХth century – 30’s of the ХХth century - Піскунов, Олександр Вікторович; Тищенко, Катерина Анатоліївна (The Journal of V. N. Karazin Kharkiv National University. Series “Philology”, 2018)
The article thoroughly analyzes the methodological foundations of the comparative-historical researches of Ukrainian linguists of the 70’s of the ХІХth century – 30’s of the ХХth century, in particular, such scientists’ as P O. Buzuk, A. Yu. Krymskyi, K. T. Nimchynov, Ye. K. Tymchenko and others. The implementation of the methodological views of these linguists in the works on the history of the East Slavic languages is studied. The innovative character of the scientists’ statements for the further development of linguistics is shown. It is proved that aforementioned Ukrainian researchers, who referred to historical and comparative methods, became the continuators of the traditions of scientists from Kharkiv, Moscow, and Kazan schools. It is defined that for the linguistic works of Ukrainian scientists of the 70’s of the ХІХth century – 30’s of the ХХth century is typical the usage of the historical (A. Yu. Krymskyi) and comparative-historical (K. T. Nimchynov) research methods. The features of the reconstruction of language phenomena, in particular, phonetic, are revealed. The important fact is that Ukrainian linguists combine the relative and absolute chronology, studying the phenomenon of vocalism and consonantism. The relevance of the in-depth study of all components of comparative-historical and historical methods in the Ukrainian linguists’ studies of the indicated period is emphasized.